2020
DOI: 10.7812/tpp/18.307
|View full text |Cite
|
Sign up to set email alerts
|

Public Health Implications of Image-Based Social Media: A Systematic Review of Instagram, Pinterest, Tumblr, and Flickr

Abstract: A retrospective cohort study, using the electronic medical records of Kaiser Permanente Northern California (2011)(2012)(2013)(2014)(2015), included 560 robotic and 6785 conventional laparoscopic cases with 1836 "complex" patients (25%). The average operative time was 152 minutes (robotic) vs 157 minutes (conventional) laparoscopic hysterectomy. Complex surgical cases averaged 190 minutes and noncomplex cases averaged 144 minutes. For women with complex disease, the robotic approach, when used by a higher-volu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 69 publications
1
44
0
6
Order By: Relevance
“…), HOs mainly use photos 54.95% of the time, in line with previous studies [24,55], while 33.45% of the posts are in link format and only 10.20% of the posts analyzed are videos ( Figure 2). These results are in line with [54], who argue that the photo format is especially appropriate for health communication. However, HOs may be missing an opportunity to enhance users' interaction, since video formats usually attract higher participation rates [25].…”
Section: Descriptive Analysissupporting
confidence: 91%
See 2 more Smart Citations
“…), HOs mainly use photos 54.95% of the time, in line with previous studies [24,55], while 33.45% of the posts are in link format and only 10.20% of the posts analyzed are videos ( Figure 2). These results are in line with [54], who argue that the photo format is especially appropriate for health communication. However, HOs may be missing an opportunity to enhance users' interaction, since video formats usually attract higher participation rates [25].…”
Section: Descriptive Analysissupporting
confidence: 91%
“…Multimedia has proven to be the format that has the potential to be engaging for users because of its direct impact on various senses [53]. The photo format, according to [54], is especially appropriate for health communication, due to its impact on people's knowledge, attitudes and perceptions regarding health issues.…”
Section: Formatmentioning
confidence: 99%
See 1 more Smart Citation
“…According to a survey conducted by the Pew Research Center in 2018, about 28% of US adults used Pinterest [18]. Although evidence has shown that intervention tactics through tailored web-based platforms can help promote evidence-based nutrition education to the public [28,29], members of the academic community have urged for more research evaluating the mutual influence between social media users and information or content providers [30]. Our study provides the first glimpse into how recipe information is disseminated and viewed from 2 distinct perspectives: Pinterest posters (pinners) and users.…”
Section: Principal Findingsmentioning
confidence: 99%
“…13 Among specific social media platforms, Instagram and Facebook have been used effectively for dissemination of public health messages and social support. 4,12,15 Despite the preference for online health support espoused by LGBTQIA+ individuals, there is relatively lesser research about the efficacy of online health care interventions with LGBTQIA+ individuals. Some guidelines have been laid out for the same.…”
Section: Introductionmentioning
confidence: 99%